Pengaruh Atribut Produk dan Promosi Melalui Media Sosial Instagram Terhadap Keputusan Pembelian Produk Waralaba Miltie bubble Di Banjarmasin Yang Di Mediasi Minat Beli - Rizki Febrianoor; Irwansyah Irwansyah; Emy Rahmawati (JURNAL BISNIS DAN PEMBANGUNAN, 2022)
This research (thesis) aims to prove and analyze the direct effect of product attributes and social media promotions on consumer purchasing decisions and also the indirect effect of buying interest on consumer purchasing decisions of Miltie bubble Banjarmasin. The research method used is associative descriptive of the relationship between variables, data collection through surveys with a sample size of 100 buyers who have seen this Miltie bubble Instagram account, the sample selected using the Purposive Sampling technique. Questionnaires were distributed through the custodians of 4 miltiebubble booths with data returning 100 people. Data analysis using Structural Equation Model based on Partial Leas Square.The results showed that respondents' responses to product attributes directly had no significant effect on purchasing decisions. Promotion through Instagram directly has a significant effect on purchasing decisions. Through buying interest, product attributes have a significant effect on purchasing decisions and can be said to be perfect mediation. Through buying interest Promotion has a significant effect on purchasing decisions and is said to be partial mediation. The results of this study can be used by companies to choose the necessary product development strategies and promotional programs that will be selected. Keywords:  Atribut Produk, Promosi Medsos, Minat Beli